FIXATION STATUS AFTER RESOLUTION OF MACULAR EDEMA ASSOCIATED WITH BRANCH RETINAL VEIN OCCLUSION. Issue 10 (October 2019) - Kogo, Takahiro; Muraoka, Yuki; Ooto, Sotaro; Suzuma, Kiyoshi; Murakami, Tomoaki; Iida, Yuto; Iida-Miwa, Yuko; Ghashut, Rima; Miyata, Manabu; Tsujikawa, Akitaka
Abstract : Purpose: To evaluate fixation status of eyes with branch retinal vein occlusion (BRVO) and to investigate its association with other clinical parameters. Methods: This study included 57 consecutive eyes with BRVO after resolution of macular edema. Fixation status was determined by microperimetry. Defect length of the foveal ellipsoid zone band was measured by optical coherence tomography, and retinal perfusion status was assessed by optical coherence tomography angiography. Results: In microperimetry, the mean fixation rate around the gravitational center of all fixation points (defined as the fixation center) was found to be 79.8 ± 18.9%, which was significantly associated with defect length of the foveal ellipsoid zone band ( P < 0.001) and distance between the foveal and fixation centers ( P = 0.012). The integrity of the ellipsoid zone band at the fixation center was intact in 55 eyes (96.5%). Fixation centers were located within and outside the foveal avascular zone in 33 (57.9%) and 24 (42.1%) eyes, respectively; among the latter eyes, all fixation centers were perfused. Downward deviation of fixation points was rare, despite variations in the occluded area; there was a significant difference in distribution of deviation between eyes with superotemporal and inferotemporal BRVO ( P < 0.001). Conclusion: In eyes with BRVO, fixation status was strongly associated with visual acuity, morphologic damage, and retinal perfusion status both in the foveal area and at the fixation center after resolution of macular edema. This information regarding fixation status could facilitate vision management in patients with BRVO. Abstract : Supplemental Digital Content is Available in the Text.In eyes with branch retinal vein occlusion, fixation status was strongly associated with visual acuity, morphologic damage, and retinal perfusion status both in the foveal area and at the fixation center when the macular edema was resolved by anti–vascular endothelial growth factor treatment.